Proposal of a photovoltaic system in areas of the technical University of Manabí - Reyes-Coveña, Jean Bryan; Gualan-Ramírez, Kevin Jaren; García-Bazurto, Andy Jamell; Quiroz-Mero, Adonis Valentín; Lituma-Ramirez, Edgar Danilo (International research journal of engineering, IT and scientific research, 2025)
Solar energy has managed to establish itself as one of the most promising and sustainable alternatives when it comes to addressing the different energy challenges at a global level, especially in developing countries, which do not have a good energy system since their electricity grids can present drawbacks. Currently, in Ecuador, periodic power outages affect both residential and educational areas, making daily activities and the development of academic projects difficult. This phenomenon is very notorious in the province of Manabí, specifically in the Technical University of Manabí, which has frequent interruptions of the electricity supply, which affects its normal operation. The aim is to propose the installation of a photovoltaic system, which is responsible for transforming solar energy into electricity, thus being a sustainable solution that, in addition to helping to reduce dependence on the conventional electricity grid, would also contribute to the transition to renewable and clean energy sources. The result was that the installation of photovoltaic systems at the Technical University of Manabí is a viable solution to counteract recurrent blackouts and move towards greater energy sustainability.